Preparation and Characterization of Proteinaceous Films from Seven Mexican Common Beans (Phaseolus vulgaris L.) - Claudia Montalvo-Paquini; Raúl Avila-Sosa; Aurelio López-Malo; Enrique Palou (Journal of Food Quality)
Bean protein concentrate (BPC) as a protein source from seven varieties of Mexican common beans (alubia, flor de mayo, garbancillo, peruano, pinto, mantequilla, and negro) was utilized for formulating edible films (EF). EF were prepared with BPC (3% w/w) and glycerol as a plasticizer by the casting method; their thickness, water content, soluble matter, protein solubility, color, puncture strength, elongation, water vapor permeability (WVP), and chemical properties (Fourier transform infrared, FTIR, and spectroscopy) were evaluated. Tested EF had an average thickness of 0.045±0.001 mm. Good stability was observed since the studied polymers did not exceed 35% of the total soluble matter while protein solubilities were not greater than 3%. EF made from peruano bean protein presented a lower value of total matter solubility (25.38±2.24%) than the other tested EF. A low value of WVP (2.06±0.25×10-10 g m/Pa s m2) was observed in films from negro bean protein, while EF from flor de mayo bean protein exhibited the highest values of puncture strength (17.35±0.82 MPa) and elongation (38.21±0.64%). Most bean protein EF had reddish or brownish color; however, films from alubia and peruano bean proteins displayed light yellowish colors. FTIR spectra of EF revealed that glycerol did not react with the studied bean proteins through covalent bonds.